A study on employer requirements towards applicants in Jobs Malaysia, Iskandar Malaysia through online advertisement / Norashikin Senin and Siti Fatimah Ibrahim - Senin, Norashikin; Ibrahim, Siti Fatimah (Faculty of Business and Management, 2014)
This study was discussed on the employer requirement towards applicants in Jobs Malaysia Iskandar Malaysia. This study analyze about the job offer in Jobs Malaysia in Johor Bahru area. Job advertisement through online has attracted job seekers especially new graduated students from universities to find any job vacancy that suits with their qualification and skills. This study gets 300 of job advertisement to be analyzed. This study analyze the job advertisement using seven elements which is skills, experiences, academic qualifications, academic courses, language, industry, and job positions. It is analyze using SPSS and the result of skill that higher demand by employer is communication and interpersonal skill, higher demand of experience is less than two years, higher demand of academic qualification is Diploma, higher demand of academic course is Business and Management, higher demand of language is Malay and English, higher demand of industry is manufacturing, and higher demand of job position is engineer.